Preliminary Study of Coral Reef Condition at the Embankment Construction Site of Pulau Harapan, Kepulauan Seribu National Park, DKI Jakarta - Tatang Mitra Setia; Hermansyah Hermansyah; Prawesti Wulandari; Hilwa Syifa Fadhillah; Cipto Utomo; Domingus Da Costa; Devi Alamsyah; Alinar Alinar (Journal of Tropical Biodiversity, 2021)
The construction of the embankment on Pulau Harapan aims to break the waves and protect the land from coastal abrasion. The construction of this embankment will provide many benefits for the community, but the implementation of its construction activities will, directly and indirectly, have an impact on the condition of the biota in the shallow sea waters of Pulau Harapan. To find out the impact of damage, it is necessary to conduct an initial study of the condition of coral reefs at the embankment construction site on Pulau Harapan. The purpose of this study is to obtain preliminary information on coral reef ecosystems. The method used in this research is the Underwater Photo Transect/UPT method which is then analyzed using CPCe 4.1 (Coral Point Count with Excel extension) software. The results of the physical and chemical measurements of the waters concluded that the quality of the waters at the observation site was still within the tolerance limits for coral life. The results of the analysis of the percentage of live coral cover are in the bad category with a percentage value of 17.1%. The composition of corals found were 5 families and 7 genera. The most commonly found coral genus is Porites. The dominance index value is 0.43 and is included in the low category and means that there is no dominant coral genus. The structure of the benthic community in the survey site area is dominated by sand and coral fragments that have been dead for a long time. The condition of the coral reef ecosystem in the observation area is classified as unstable.